Measuring livelihood resilience of farmers and diagnosing obstacle factors under the impact of COVID-19 in Jiangsu Province, China - Hu, Chao; Dong, Jiayun (Frontiers in Sustainable Food Systems, 2023)
Research on livelihood resilience not only helps to understand the adverse impact of COVID-19 on farmers' livelihoods, but also helps to formulate concrete actions to enhance the resilience of farmers' livelihoods and support economic recovery. Taking rural residents in Jiangsu Province of China as an example, this paper uses one-way ANOVA, entropy method and obstacle degree models to quantitatively analyze the characteristics of livelihood resilience of different types of farmers and the main obstacle factors. The main findings are as follows: (1) Both laboring type and part-time type farmers together accounted for 75.98% of the survey sample, and the non-agricultural phenomenon of farming households in Jiangsu Province is obvious; There are significant differences in livelihood characteristics among different types of farmers, with relatively high livelihood capital for planting and breeding type farmers and relatively low livelihood capital for asset and subsidy type farmers. (2) The livelihood resilience of farmers in Jiangsu Province from high to low is breeding type farmers (0.501), planting type farmers (0.493), laboring type farmers (0.465), part-time type farmers (0.455), subsidy type farmers (0.400), asset type farmers (0.389). (3) In the diagnosis of barrier factors of livelihood resilience, buffer ability disorder is the most obvious, learning ability disorder is the second, and self-organization ability disorder is the last; Among the specific factors, the most important obstacle factors for planting, breeding and asset type farmers are the number of productive assets, the number of agricultural technical services for laboring type farmers, the number of channels for obtaining information for part-time type farmers, and the family labor income for subsidy type farmers. Therefore, it is recommended that policies be improved in the post-epidemic era in terms of raising farmers' livelihood capital, developing knowledge and skills for learning, and enhancing organizational awareness.